The prognostic value of ultrasound features and parafibromin expression in parathyroid carcinoma - Ruifeng Liu; Liyuan Ma; Yu Xia; Luying Gao; Jiang Ji; Yuang An; Aonan Pan; Nengwen Luo; Yuxin Jiang (Orphanet Journal of Rare Diseases)
Abstract Objectives To investigate prognostic factors related with parathyroid carcinoma (PC) based upon ultrasound (US) parameters and parafibromin expression. Methods Between 2000/01 and 2022/07, thirty-four PC patients with detailed preoperative ultrasonography were enrolled in the research. Immunohistochemical staining of parafibromin was performed on pathological samples of these patients. Based on the expression of parafibromin, the cases were divided into a positive control group (parafibromin expression ≥ 10%) and a negative experimental group (parafibromin expression < 10%). The ultrasound and clinical features of the two groups were analyzed, and Cox regression was used to identify the independent prognostic factors regarding disease-free survival (DFS) and overall survival (OS). Results Among 34 patients with parathyroid carcinoma, 26 (76.5%) were parafibromin-positive, while 8 (23.5%) were parafibromin-negative. The mean follow-up time was 72.6 (11.0-179.3) months. During the overall survival period, 7 cases (20.6%) died, and 9 cases (26.5%) experienced recurrence or metastasis. The median overall survival time (interquartile range) was 65.7 (35.5–89.7) months, and the median disease-free survival time (interquartile range) was 38.2 (22.2–69.7) months. The risk of recurrence and metastasis in the parafibromin-negative group was 5.9 times higher than that in parafibromin-positive group (95% CI 1.569–22.190). PC patients with calcification on preoperative ultrasonography had a 9.4 times higher risk of death during the overall survival period compared with patients without calcification (95% CI 1.037–85.915). However, parafibromin expression did not show a significant impact on the prognosis of the overall survival. Conclusions Preoperative US-detected calcification within the lesion is an independent risk factor indicating the shorter OS for PC patients, while loss of parafibromin expression is significant for indicating the recurrence or metastasis of PC patients.